A simple method for preparing ZnO foam/carbon quantum dots nanocomposite and their photocatalytic applications. (1st June 2016) - Ding, Delei; Lan, Wei; Yang, Zhiwei; Zhao, Xiaohua; Chen, Youxin; Wang, Junya; Zhang, Xuetao; Zhang, Yue; Su, Qing; Xie, Erqing
Abstract: ZnO foam/carbon quantum dots (CQDs) nanocomposite has been successfully synthesized by a facile process which ZnO foam prepared by combustion method was dispersed in CQDs solution. It is found that the ZnO foam is constructed by a large number of ZnO nanoparticles filling in irregular, hierarchical pores. The foam structure originates from a large amounts of gas produced in the combustion process. The obtained ZnO foam/CQDs nanocomposite shows excellent photocatalytic activities on degrading Rhodamine B (RhB), Methyl orange (MO) and Methylene blue (MB) under UV and visible light irradiation. The order of degradation efficiency is MB>RhB>MO. It is attributed to the synergistic effect of several factors, including the light-trapping effect of ZnO foam, the up-converted photoluminescence behavior and photo-induced electron transfer property of CQDs.